Epithelial regenerative activity of topic administration of canine adipose-derived mesenchymal stem cells secretome in eye drops format—an in vitro study - Carrera, Alefe Luiz Caliani [UNESP]; de Araújo, Gustavo Soares; Sena Brunel, Hilana Dos Santos; Malard, Patrícia Furtado; de Andrade, Rosângela Vieira; Alecrim, Milena Zorante; Minto, Bruno Watanabe [UNESP] (AME Publishing Company, 2025)
Background: The adipose-derived mesenchymal stem cells secretome is responsible for the paracrine action of cellular and tissue regeneration signaling, with the epithelium being a key target. The corneal epithelium’s injuries are one of the main casuistry of lesions in veterinary ophthalmology, and also occur in humans, being a challenge for re-epithelization. In this field, the topic administration of secretome from adipose-derived stem cells may act to enhance tissue repair. This way, analyzing the adipose-derived stem cells secretome’s in vitro potential, as eye drops, for HaCaT cells, is a promising study and was the aim of this paper. Methods: For that, three cells batches were used, their secretomes were homogenized and originated C1, C2 and C3 eye drops. The epithelial tissue was obtained from HaCaT culture in laboratory. Metabolic activity through MTT and microscopic scratch-wound assays were conducted, as well as cellular replication proofs in Neubauer chamber, for control and treat groups. Results: As results, there were found that all secretomes eye drops were able to improve cellular metabolic activity (P=0.02) and accelerate scratch-wound closure through a higher cellular migration, resulting in 30% faster time against the control group (P<0.001, P=0.001 and P=0.003, respectively). For cellular replication, C1 and C2 groups were significantly higher than control one (P=0.01 and P=0.002, respectively), while C3 did not differ (P=0.09). Conclusions: It was concluded that adipose-derived stem cells secretome’s eye drops is able to accelerate epithelial cell metabolism for replication and the wound repair through cellular migration and may figure as an important additional pharmacological issue to epithelial corneal injuries repair.
Keywords: Corneal epithelium; HaCaT cells; mesenchymal stem cells; migration test; scratch wound assay